Avalia????o do disp??ndio de energia e fadiga muscular em pacientes com doen??a pulmonar obstrutiva cr??nica ap??s atividade f??sica com o videogame - Tobelem, Daysi da Cruz (2015)
Introduction: Chronic obstructive pulmonary disease (COPD) is characterized by both pulmonary manifestations as systemic. To maintain or improve the functional capacity and quality of life is already proven the role of physical exercises for these patients as a mechanism to delay the onset of symptoms of this disease limiting. Justified study the feasibility of the use of an interactive video game, as an auxiliary resource for rehabilitation of these patients. Objective: to analyze the energy expenditure and muscle fatigue of the rectus femoral muscle of patients with COPD and elderly people matched by age after performing an activity with the Videogame Xbox-360. Method: We conducted a study of type randomized clinical trial, which was attended by 13 volunteers both with COPD as of 13 healthy individuals (matched for age). The study was conducted in the laboratory of Functional Respiratory Assessment (LARESP) on three different days, respiratory function and strength assessment, functional capacity and quality of life. In the remaining days, intervention protocols were applied, which featured the electromyographic assessment of the Rectus Femoris and the implementation of the proposed activity along with the analysis of the training intensity and energy expenditure. Results: It was observed significantly greater energy expenditure after physical activity both for patients with COPD (3,72??1,04 vs 5,22 ??1,21, treadmill and videogame) as by healthy individuals (2,87??0,62 vs 3,49??0,75). Regarding the evaluation of heart rate during training, there was no significant difference as heart rate (HR) training, average and peak even while performing the activities, by all study participants. Regarding the electromyographic evaluation of the rectus femoris muscle, it can be observed reduction of the variable median frequency (MF) after conducting both activities and both the groups, however, in relation to the healthy elderly, it can be seen higher reduction in MF after carrying out the activity on the treadmill, the same did not occur in patients with COPD. Conclusions: These results allowed us to conclude that the practice of physical activities using the video game may be an alternative applied both in the rehabilitation of patients with COPD as the training of healthy elderly.